Development of a tourist application, based on app, as a support for training in the programs of the regional San Andres - Pérez Garcia, Tatiana
This article presents the design and development of a mobile application that supports the formation of the tourism area of the Tourist Training Center, Seafarers and Services. The application allows apprentices and instructors in this area to perform metrics and obtain reports according to the search filters and the parameterization of the information collected from forms, geolocation and multimedia material. Its method is focused on the conception of the methodologies agiles, this in order to define the characteristics or environment of the application. The result of this work was the construction of an integrated system that allows access to information in real time, with permanent updating that allows decisionmaking and serves as a tool of orientation for the design of products and services in the hands of the productive sector.